Discrete mellin convolution with dilation and its applications - Plaschinsky, Pavel V. (Mathematical Modelling and Analysis, 1998)
The analysis of the discrete Mellin convolution is given. A generalization of rezults from [4,5] is presented. Some applications illustrate the efficiency of proposed methods. First Published Online: 14 Oct 2010